The Semantic Realism/Anti-Realism Dispute and Knowledge of Meanings - Panu Raatikainen (Baltic International Yearbook of Cognition, Logic and Communication, 2009)
Here the relationship between understanding and knowledge of meaning is discussed from two different perspectives: that of Dummettian semantic anti-realism and that of the semantic externalism of Putnam and others. The question addressed is whether or not the truth of semantic externalism would undermine a central premise in one of Dummett’s key arguments for anti-realism, insofar as Dummett’s premise involves an assumption about the transparency of meaning and semantic externalism is often taken to undermine such transparency. Several notions of transparency and conveyability of meaning are distinguished and it is argued that, though the Dummettian argument for anti-realism presupposes only a weak connection between knowledge of meaning and understanding, even this much is not trivially true in light of semantic externalism, and that semantic externalism, if true, would thus represent a reason for rejecting the crucial assumption on which the Dummettian argument depends.